Efficacy and safety of propranolol on the proliferative phase of infantile hemangioma: A hospital-based prospective study - Jignaben Krunal Padhiyar; Nayan H Patel; Trusha P Gajjar; Mansi D Buch; Yogesh B Shah; Rekha Solanki (Wolters Kluwer Medknow Publications, 2018)
Background: Propranolol may be more effective and safer than previously established therapies, and it may be used as a first-line therapy for infantile hemangioma (IH). Propranolol is thought to inhibit the growth of blood vessels by decreasing vascular endothelial growth factor. Aims and Objectives: The aim of this study is to study the efficacy and safety of propranolol in IH and for standardization of dose in tablet form. Materials and Methods: A total of 23 patients with 30 IH s were recruited in the study prospectively, after ruling out any contraindications for oral propranolol and obtaining consent from parents. Patients with <7 kg weight were given oral propranolol 5 mg twice daily and >7 kg weight were given 5 mg thrice daily. Patients were evaluated according to visual analog scale and ultrasonographically on day 0, day 30, day 60, and day 90. Results: Out of a total of 30, 25 (83.33%) were superficial, 3 (10%) were deep, and 2 (6.66%) were mixed hemangioma. All patients with superficial hemangiomas showed a change in the color of the lesion and arrest of growth within the 1st month of therapy and a gradual decrease in size was noticed in 23 (92%, n = 25) patients during the study period except in 2 (8%). Complete clearance was noticed in 68% of patients of superficial hemangioma at the end of the study period. Out of 25 patients, a total of 5 (20%) patients had ulceration at the time of presentation which started to heal within 15 days of therapy. Five (16.66%, n = 30) patients with deep and mixed variety showed arrest of growth but no decrease in size. No side effects were seen except temporary coldness of extremity in 1 (3.33%) patient. Conclusion: Propranolol is safe and effective for treatment of proliferative phase of superficial hemangiomas with very less side effects compared to oral steroids and other recommended therapies, and unavailability of syrup can be overcome by giving tablet in fixed dosage.